Mapeo de políticas colombianas e instrumentos de política relacionados con tierra, agua y alimentación (1991 a 2022) - Castro Nunez, Augusto Carlos; Gonzalez Rojas, Maria Carolina; Buritica Casanova, Alexander; Centro de Investigacion en Sistemas Agroalimentarios (2024)
The data collection objective was to map Colombian national policies and policy instruments related to land, water and food issues. The database presents detailed information on national policies and policy instruments such as, the policy sector, the objective, the year. This data collection were used to lead policy coherence analysis among and between land, water and food policy domains. Metodology: The methodology used was policy mapping